POLA ASUH ORANG TUA DALAM PENCEGAHAN STUNTING UNTUK ANAK USIA DINI DI KELURAHAN FAOBATA - Herkulianan Natalia Wena; Yasinta Maria Fono; Karmelia Rosfinda Meo Maku; Elisabeth Tantiana Ngura (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the parenting style of parents in the prevention of stunting in early childhood in Faobata Village and identify various challenges faced in daily parenting practices. Stunting is a chronic nutritional problem that not only affects children's physical growth, but also impacts cognitive development and the quality of human resources in the future. Therefore, parenting that includes the fulfillment of nutrition, health and hygiene, and psychosocial stimulation is an important factor in stunting prevention efforts. This study uses a qualitative approach with a case study design. The research subjects consisted of five parents who had children identified as stunting and were selected through purposive sampling techniques. Data was collected through participatory observation, in-depth interviews, and documentation, then analyzed descriptively through the stages of data reduction, grouping of findings, and drawing conclusions. The results of the study show that parents have tried to provide food regularly, maintain children's hygiene, and show good emotional attention. However, nutritional variation and balance have not been optimal, health monitoring visits have not been carried out consistently, and developmental stimulation is still spontaneous and unplanned.